2012
DOI: 10.1037/a0024927
|View full text |Cite
|
Sign up to set email alerts
|

Coping and mental health outcomes among israelis living with the chronic threat of terrorism.

Abstract: Relatively little is known about how people cope with the chronic threat of terrorism or how coping behaviors relate to mental health outcomes within this context. Through the use of exploratory factor analysis, we identified seven latent coping factors among Israeli citizens living near the Gaza border, a region that has been regularly subjected to rocket and mortar attacks. Moderation analysis revealed that three coping factors (substance use coping, denial/disengagement, and social support seeking) exacerba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Studies of terrorism and natural disasters in general population samples have found short-term increases in mean population alcohol consumption (DiMaggio et al, 2009; Keyes et al, 2011), but have rarely found increases in alcohol disorders (North et al, 2004, 2010, 2002). Small studies of civilian samples find that exposure to war and terrorism are associated with psychological distress (Dickstein et al, 2012; Hobfoll et al, 2012), but wartime experiences as risk factors for alcohol use disorders in civilian populations remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of terrorism and natural disasters in general population samples have found short-term increases in mean population alcohol consumption (DiMaggio et al, 2009; Keyes et al, 2011), but have rarely found increases in alcohol disorders (North et al, 2004, 2010, 2002). Small studies of civilian samples find that exposure to war and terrorism are associated with psychological distress (Dickstein et al, 2012; Hobfoll et al, 2012), but wartime experiences as risk factors for alcohol use disorders in civilian populations remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research by Dickstein et al (2012) on coping strategies with continuous traumatic stress (e.g., terrorism) of Israelis found that substance use coping, denial/disengagement and social support seeking strategies were all associated with psychiatric symptoms, and the only coping strategy found to be protective strategy was acceptance and positive reframing (see also Nuttman-Shwartz & Dekel, 2009). Positive reappraisal, being optimistic, and possessing a futuristic orientation have been significantly negatively correlated with AA and depression (e.g., Kira et al, 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…Drinking appears to be a social activity, rather than a solitary one (Bloomfield, Stockwell, Gmel, & Rehn, 2003). Drinking in Israelis may not function as a coping mechanism in the same way as in the U.S. (Bleich et al, 2003; Dickstein et al, 2012), and may also differ by mental health factors (Bleich, Gelkopf, Melamed, & Solomon, 2006; Kane et al, 2014). In other societies, individuals experiencing stressful past or terrorist events were found to drink more alcohol, including in U.S. studies of the effects of September 11 th (Richman et al, 2008) and the effects of war on returning veterans (Benyamini & Solomon, 2005).…”
Section: Discussionmentioning
confidence: 99%